Preventing a U.S. Fiscal Crisis: An Experiment in Political Economy - Larson, Sven R (Journal of Management Policy and Practice, 2019)
This paper investigates the potential for a fiscal crisis of European nature in the United States. The paper uses the crisis in Greece as a case study to identify three necessary conditions for a crisis. Based on those conditions and on observed fiscal similarities between Greece and the United States, the paper defines a fiscal crisis as a policy problem and explains why it cannot be properly addressed within the confinements of mainstream methodology in economics.